Yield and photosynthetic attributes of sunflower cultivars grown under supplemental irrigation in the semiarid region of the Brazilian Northeast - Carvalho, Luciana Marques de; Carvalho, Hélio Wilson Lemos de; Carvalho, Claudio Guilherme Portela de (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to identify the sunflower (Helianthus annuus) cultivar with the highest yield potential for cultivation in the semiarid region of the Brazilian Northeast, under field conditions, with supplementary irrigation. Plant photosynthetic performance and yield were determined in field trials. The experiments were carried out in a randomized complete block design with 12 cultivars planted at 0.70x0.30 m. Net photosynthetic rates above 27 µmol m-2 s-1 and average achene yield of 2,364.68 kg ha-1 and oil yield 961.96 of kg ha-1 were determined. This performance was achieved due to: high stomatal conductance in ’Aguara 4’, ’BRS 322’, and ’CF101’, low water loss through transpiration in ’M 734’, ’BRS 321’, ’BRS 324’, ’BRS 387’, and ’Helio 251’, or high-intrinsic photosynthetic efficiency in ’Helio 251’ and ’BRS 387’. Most cultivars provided grain amounts and oil contents similar to those of cultivars grown in the largest Brazilian producing areas. The cultivars that provide the highest yield in the Brazilian semiarid region, when grown under supplementary irrigation, are ’Aguara 4’, ’CF 101’, and ’BRS 322’ with a high achene and oil yield, and ’M 734’ with high achene yield. The less susceptible cultivars to severe water deficit are ’Helio 251’ and ’BRS 387’ with a high-intrinsic photosynthetic efficiency.